Mohammad Isa Anshary's Struggle: Islamic Thought and Political Strategy in Facing the Spread of Communism in Indonesia 1950 – 1969 - Hidayat, Asep Ahmad; Maulana, Ilham; Syah, Muhammad Kautsar Thariq; Al Fahmi, Ibrahim Nasrul Haq; Arsyad, Muhammad Fikri (UIN Sunan Gunung Djati Bandung, 2025)
The aim of this research is to find out the struggle, thoughts and political strategies of one of the Masyumi party figures, namely Mohammad Isa Anshary, in opposing the spread of communist ideology in Indonesia. This research uses historical methods through four stages, namely heuristics, criticism, interpretation and writing. The data processing technique in this research is descriptive qualitative, namely data analysis simultaneously with data collection. The results of this research show that the figure of Isa Anshary, who is a Masjumi party politician and general chairman of a religious movement in Indonesia, namely Islamic Unity, has a very central role in defending Islamic ideology from attacks by communist ideology which destroys the order of religious, national and state life. He is positioned as a radical Islamic fundamentalist figure because of his uncompromising nature regarding Islam ideology. It is hoped that this research will provide readers with insight into the importance of Islamic political struggles in Indonesian history, as well as their impact on national political dynamics. appreciates the contribution of great figures such as Mohammad Isa Anshary who may be less known to the younger generation, especially his role in opposing the spread of communist ideology in Indonesia and provides an opportunity for readers to reflect on and study Islamic thought in a political and social context. This research presents a reinterpretation of the role, thoughts and political strategies of Mohammad Isa Anshary in the Indonesian political movement, especially in facing the threat of communism which grew rapidly after independence, through efforts to consolidate the Islamic political power he built. So far, many studies have focused more on big figures such as Sukarno, Hatta, or other military figures, while the role of figures such as Isa Anshary, who contributed to Islamic thought and political strategy, often receives less attention.